2016
DOI: 10.1038/srep26866
|View full text |Cite
|
Sign up to set email alerts
|

Vagus Nerve Stimulation Exerts the Neuroprotective Effects in Obese-Insulin Resistant Rats, Leading to the Improvement of Cognitive Function

Abstract: Vagus nerve stimulation (VNS) therapy was shown to improve peripheral insulin sensitivity. However, the effects of chronic VNS therapy on brain insulin sensitivity, dendritic spine density, brain mitochondrial function, apoptosis and cognition in obese-insulin resistant subjects have never been investigated. Male Wistar rats (n = 24) were fed with either a normal diet (n = 8) or a HFD (n = 16) for 12 weeks. At week 13, HFD-fed rats were divided into 2 groups (n = 8/group). Each group was received either sham t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 36 publications
1
32
0
Order By: Relevance
“…Obese-insulin resistance caused by HFD consumption not only induced systemic inflammation, but also caused brain inflammation, as shown by increased brain pro-inflammatory cytokine; TNF-α and a transcriptional factor; NF-κB ( 13 , 15 , 19 , 116 ). Furthermore, brain oxidative stress was shown by an elevation in cytotoxic aldehyde products; MDA was also found in association with the brain inflammation following obese-insulin resistance ( 8 , 11 , 13 15 , 19 , 28 31 ).…”
Section: Peripheral Insulin Resistance Induced Brain Insulin Resistanmentioning
confidence: 99%
See 1 more Smart Citation
“…Obese-insulin resistance caused by HFD consumption not only induced systemic inflammation, but also caused brain inflammation, as shown by increased brain pro-inflammatory cytokine; TNF-α and a transcriptional factor; NF-κB ( 13 , 15 , 19 , 116 ). Furthermore, brain oxidative stress was shown by an elevation in cytotoxic aldehyde products; MDA was also found in association with the brain inflammation following obese-insulin resistance ( 8 , 11 , 13 15 , 19 , 28 31 ).…”
Section: Peripheral Insulin Resistance Induced Brain Insulin Resistanmentioning
confidence: 99%
“…Previous studies reported that mitochondrial dysfunction has been related to the development of insulin resistance ( 26 , 27 ). Interestingly, it has been shown that brain mitochondrial dysfunction, as indicated by the overproduction of mitochondrial reactive oxygen species (ROS), mitochondrial depolarization and mitochondrial swelling, has occurred in association with brain insulin resistance and all of these events could lead to the development of cognitive decline and Alzheimer's disease ( 6 , 8 , 11 , 13 15 , 19 , 28 31 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported that vagus nerve stimulation has beneficial effects on cognitive functions [71][72][73]. However, established procedures to stimulate the vagus nerve require surgery to implant electrophysiological devices, implicating safety and complication risks.…”
Section: Mhbas Enhance Cognitive Function Via Activation Of the Vagusmentioning
confidence: 99%
“…Neuroprotection is mainly determined using behavioral activity tests of an animal model as well as biochemical assays (for example, of inflammatory cytokines and oxidative stress factors) using the tissues of animal models. Animal models have greatly advanced the understanding of AD pathogenesis (Phillips, Michell, Pruess, & Barker, ), and many animal studies have examined neuroprotective peptides (Chunchai et al., ; Nagahara et al., ; Wang et al., ). Behavioral studies in animal models of neurodegenerative disease have mainly been conducted using the Morris water maze test, probe trial, passive avoidance test, and locomotor activity tests.…”
Section: Determination Of Neuroprotective Effect Of Peptides/hydrolysmentioning
confidence: 99%